If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(1 + -1r) + -8r = -2(r + -1) (1 * -2 + -1r * -2) + -8r = -2(r + -1) (-2 + 2r) + -8r = -2(r + -1) Combine like terms: 2r + -8r = -6r -2 + -6r = -2(r + -1) Reorder the terms: -2 + -6r = -2(-1 + r) -2 + -6r = (-1 * -2 + r * -2) -2 + -6r = (2 + -2r) Solving -2 + -6r = 2 + -2r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '2r' to each side of the equation. -2 + -6r + 2r = 2 + -2r + 2r Combine like terms: -6r + 2r = -4r -2 + -4r = 2 + -2r + 2r Combine like terms: -2r + 2r = 0 -2 + -4r = 2 + 0 -2 + -4r = 2 Add '2' to each side of the equation. -2 + 2 + -4r = 2 + 2 Combine like terms: -2 + 2 = 0 0 + -4r = 2 + 2 -4r = 2 + 2 Combine like terms: 2 + 2 = 4 -4r = 4 Divide each side by '-4'. r = -1 Simplifying r = -1
| 3x+14=x-28 | | u^2-14u+49=2u^2-19u+55 | | (2x-25)(x+10)=0 | | x^2-11x+17=0 | | 5y-10y=7y+18 | | -7n+26=4(1+n) | | 16x-5=4x+19 | | 5-2x=3(x+2) | | 2x-x=13n | | 6(2x+3y)+3(x-y)= | | 2x+9=5x+3 | | 4(x-8)=-8+x | | 9x+32y=32 | | -32-5x= | | 5*5=2581 | | -18x^2-48x-50=0 | | 2x^2+5x=250 | | n^2-n-10=-10 | | 6(n+2m)+m= | | p^2+12p+21=-6 | | n^2=-35-12n | | 22-4x=66+7x | | 12r=-27-r^2 | | x^2+13x=-36 | | 5x-19=2x-18 | | 0=-b^2+25 | | 14+x+14=-20x-20 | | 10x+2(3)+5x-2= | | x^2+6x-4=-9 | | p-1-5p+3p=8 | | 1+4a=-a-14 | | 4x^2+64-252=0 |